Political theology of Kierkegaard - Das, Saitya Brata (New perspectives in ontology., 2020)
Berger and Whistler provide a ground-breaking account of Schelling's first controversy with his critic A.C.A. Eschenmayer in 1801, which focused on the philosophy of nature. They argue that key Schellingian concepts, such as identity, potency and abstraction, were first forged in his early debate with Eschenmayer.